Internetinių svetainių kūrimo ir pritaikymo mobiliesiems įrenginiams technologijos įmonėje UAB „Orca team“ - Martinkaitis, Dovydas (Institutional Repository of Kaunas University of Technology, 2015)
The final project of the bachelor's thesis analyses the development of Internet websites and their applications to mobile devices following the pattern at the Joint Stock Company \"ORCA Team. The beginning of the thesis, the first section, looks into the chosen technologies and reasons their importance. It also looks into the stages of website development and the cycle that involves both equipment and the technological process. The section emphasizes the importance of adaptable websites to modern ones The second section discusses the vision of website development and designs a technological process. Precise estimations are analysed and described in detail thus reasoning every stage of the technological process. This section provides the descriptions of quality control. Having summarized the estimates, it presents the numbers of equipment and the staff, designs the premises for the technological process to be performed. The third section presents the decriptions of occupational safety and ecology. It gives safety regulations and the ecology compliance plan of the company. The final section carries out a quantitative marketing research to assess the consumer satisfaction with the sevices. The results are summarized thus providing data analysis. The results are summarized in the conclusions which also give development recommendations to the Joint Stock Company “ORCA Team“.